FoxP1 is a transcriptional repressor associated with cancer cachexia that induces skeletal muscle wasting and weakness. Issue 2 (1st February 2021) - Neyroud, Daria; Nosacka, Rachel L.; Callaway, Chandler S.; Trevino, Jose G.; Hu, Hui; Judge, Sarah M.; Judge, Andrew R.
Abstract: Background: Skeletal muscle wasting is a devastating consequence of cancer that affects up to 80% of cancer patients and associates with reduced survival. Herein, we investigated the biological significance of Forkhead box P1 (FoxP1), a transcriptional repressor that we demonstrate is up‐regulated in skeletal muscle in multiple models of cancer cachexia and in cachectic cancer patients. Methods: Inducible, skeletal muscle‐specific FoxP1 over‐expressing (FoxP1 iSkmTg/Tg ) mice were generated through crossing conditional Foxp1a transgenic mice with HSA‐MCM mice that express tamoxifen‐inducible Cre recombinase under control of the skeletal muscle actin promoter. To determine the requirement of FoxP1 for cancer‐induced skeletal muscle wasting, FoxP1‐shRNA was packaged and targeted to muscles using AAV9 delivery prior to inoculation of mice with Colon‐26 Adenocarcinoma (C26) cells. Results: Up‐regulation of FoxP1 in adult skeletal muscle was sufficient to induce features of cachexia, including 15% reduction in body mass ( P < 0.05), and a 16–27% reduction in skeletal muscle mass ( P < 0.05) that was characterized by a 20% reduction in muscle fibre cross‐sectional area of type IIX/B muscle fibres ( P = 0.020). Skeletal muscles from FoxP1 iSkmTg/Tg mice also showed significant damage and myopathy characterized by the presence of centrally nucleated myofibres, extracellular matrix expansion, and were 19–26% weaker than controls ( P < 0.05). Transcriptomic analysis revealed FoxP1 as a potent transcriptional repressor of skeletal muscle gene expression, with enrichment of pathways related to skeletal muscle structure and function, growth signalling, and cell quality control. Because FoxP1 functions, at least in part, as a transcriptional repressor through its interaction with histone deacetylase proteins, we treated FoxP1 iSkmTg/Tg mice with Trichostatin A, and found that this completely prevented the loss of muscle mass ( p = 0.007) and fibre atrophy ( P < 0.001) in the tibialis anterior . In the context of cancer, FoxP1 knockdown blocked the cancer‐induced repression of myocyte enhancer factor 2 (MEF2)‐target genes critical to muscle differentiation and repair, improved muscle ultrastructure, and attenuated muscle fibre atrophy by 50% ( P < 0.05). Conclusions: In summary, we identify FoxP1 as a novel repressor of skeletal muscle gene expression that is increased in cancer cachexia, whose up‐regulation is sufficient to induce skeletal muscle wasting and weakness, and required for the normal wasting response to cancer.